2023
DOI: 10.3390/ijms24043841
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters in Prevention and Treatment of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most frequent cause of cognitive impairment in middle-aged and older populations. There is a lack of drugs that demonstrate significant efficacy in AD, so the study of the pathogenesis of AD is of great importance. More efficacious interventions are needed, as reflected by our population’s fast aging. Synaptic plasticity is the capacity of neurons to adjust their connections, and it is strongly tied to learning and memory, cognitive function, and brain injury recovery. Changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…The neurotransmitter imbalances linked to Alzheimer's disease (AD) include disturbances in the cholinergic, serotonergic, noradrenergic, and dopaminergic systems [8]. In patients with AD, these imbalances play a role in neuropsychiatric symptoms and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The neurotransmitter imbalances linked to Alzheimer's disease (AD) include disturbances in the cholinergic, serotonergic, noradrenergic, and dopaminergic systems [8]. In patients with AD, these imbalances play a role in neuropsychiatric symptoms and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological perturbations of neurotransmitter systems are believed to play a role in the development of Alzheimer's neuropathology and includes, loss of monoaminergic neurons, decreased monoamine levels, decreased γ‐Aminobutyric acid (GABA) levels, dysfunction of glutamatergic neurons, and loss of cholinergic neurons (Yang et al., 2023). Both animal and human studies have demonstrated a role for monoamine neurotransmitters in the development of Alzheimer's disease (Reddy et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of individuals suffering from AD is a great concern for healthcare organizations worldwide. Current treatments are palliative and only modulates symptoms or at best slows the progression of disease. Preventive or long-term strategies are currently lacking . Many studies have highlighted the role of soluble prefibrillar Aβ-oligomers as culprits that disrupt normal neuronal function and structure by damaging cellular components through various pathways .…”
Section: Application Of Cpps To Prevent Neuronal Degenerationmentioning
confidence: 99%